2021
DOI: 10.1002/jaba.870
|View full text |Cite
|
Sign up to set email alerts
|

Accumulated and distributed response–reinforcer arrangements during the treatment of escape‐maintained problem behavior

Abstract: Contingent positive reinforcement has proven more effective in treating escape-maintained problem behavior than contingent negative reinforcement, particularly when problem behavior continues to produce escape. However, this research has overwhelmingly used distributed-reinforcement arrangements, where tasks and reinforcer access are interspersed throughout the work period. An alternative to interspersal involves allowing the individual to accumulate and then receive a larger quantity of reinforcement once wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Similar to the results of Frank-Crawford et al (2021), we did not find any difference between delivery methods. It is possible that the consummatory behavior of the dogs in the current study did not vary significantly between delivery methods, given that the treats were relatively small and consuming all four treats at once likely did not take the dogs any longer than four treats one-by-one, nor did dogs move away to eat and then return to gather the next piece of food as did some animals in prior studies (e.g., Amsel et al, 1968).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Similar to the results of Frank-Crawford et al (2021), we did not find any difference between delivery methods. It is possible that the consummatory behavior of the dogs in the current study did not vary significantly between delivery methods, given that the treats were relatively small and consuming all four treats at once likely did not take the dogs any longer than four treats one-by-one, nor did dogs move away to eat and then return to gather the next piece of food as did some animals in prior studies (e.g., Amsel et al, 1968).…”
Section: Resultssupporting
confidence: 89%
“…The relative efficacy of accumulated reinforcers could be due to continuity of access, such that engaging longer with food when presented differently (one large vs. many small items) could produce similar differences in reinforcer efficacy. However, Frank-Crawford et al (2021) investigated accumulated and distributed food reinforcers for children and found that accumulated food and distributed food were equally effective for all four learners.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations